Avaliação neutrônica da inserção de veneno queimável em reator a água pressurizada - Rochkhudson Batista de Faria (2013)
The development of this work was to match the "Burn-up Credit Criticality Benchmark - Phase II-D - PWR-UO2 Assembly Study of Control Rod Effects on Spent Fuel Composition" (case 15), which was modeled using the code MCNP5 and SCALE 6.0. The results of the infinite multiplication factor (kinf) were compared with those obtained by international institutions. Later we performed in this same benchmark, a sensitivity analysis using SCALE 6.0. Thus, we tested several changes in case 15 of Benchmark, such as insertion of different percentages of burnable poison, changing the number and positions of the rods. In all cases were analyzed, comparisons and discussions about the results. The same methodology was applied to the reactor core of the Nuclear Plant in Brazil, Angra II, initially to evaluate its behavior when subjected to a variation in the percentage of burnable poison and then, introduce changes also in the enrichment of nuclear fuel, doing the appropriate comparisons of results. Considering results and experience gained, the Department of Nuclear Engineering, is prepared to control analysis of reactivity with the use of different types of burnable poisons under the code SCALE 6.0 through its various modules.